Acquired tonsillar herniation related to spontaneous intracranial hypotension: case reports - Chen, Lili; Wu, Haijian; Hu, Xingyue; Ying, Guangyu (Frontiers in Neurology, 2024)
Background Acquired prolapse of the cerebellar tonsils in spontaneous intracranial hypotension (SIH) patients is rare. This study aims to evaluate neuroimaging changes of acquired prolapse of the cerebellar tonsils below the foramen magnum in SIH patients due to spontaneous spinal cerebrospinal fluid leakage, which was treated by targeted epidural blood patches (EBP). Methods We retrospectively reviewed clinical and neuroimaging characteristics of 5 cases of SIH with acquired prolapse of the cerebellar tonsils that received targeted EBP in our institution from January 2013 to December 2016. Results Of these SIH patients, all of them suffered from an orthostatic headache. Initial cranial MRI demonstrated descent of the cerebellar tonsils ≥5 mm. Intrathecal gadolinium-enhanced spinal MR myelography and/or spinal MR hydrography were performed to evaluate the level of spinal cerebrospinal fluid leakage. Symptoms were alleviated in all 5 patients after two (n = 4), or three (n = 1) targeted EBP during hospitalization. Follow-up cranial MRI revealed that the descent of cerebellar tonsils was reversed after EBP treatment. Conclusion Acquired tonsillar herniation can occur in patients with SIH and spinal cerebrospinal fluid leakage. Symptoms of these patients may be resolved and radiologic findings may be reversed after EBP treatment.